Combination of STAT3 targeting oligonucleotides with PD-L1 inhibitors - ABRAMS MARK; GANESH SHISHIR (2024)
The subject matter disclosed herein relates to modulating gene expression using siRNA compositions and methods that involve affecting key cell populations that support cancer growth and metastasis to affect beneficial treatment, alleviation or removal of potential tumors in a patient. 本文公开的主题涉及使用siRNA组合物和方法调节基因表达，所述siRNA组合物和方法涉及影响支持癌症生长和转移的关键细胞群体，以影响患者中潜在肿瘤的有益治疗、缓解或去除。